Membentuk Karakter Anak Usia Dini Melalui Kegiatan dan Metode Pembelajaran Berbasis Keagamaan di TK Miftahul Huda Kota Kediri - Ridwanulloh, M. Ubaidillah; Thoriqsi, Salsa (Insititut Agama Islam Negeri (IAIN) Curup, 2024)
The process of cultivating character in early childhood is not easy and requires efforts with various strategies to produce results. Miftahul Huda Kindergarten is one of the best educational institutions and is most popular with the local community. Among the attractions is character building, which is carried out at Miftahul Huda Kindergarten with religious-based activities and learning methods. The aim of this research is to describe methods for forming early childhood character through religious-based activities and learning methods. This research method uses descriptive and qualitative methods. Data sources were obtained through observation, interviews, and documentation. Interview informants were school principals, teachers, and student parents. The results of the research are methods for forming character in early childhood that are used by teachers through religious activities such as praying with the teacher, sharing with each other, getting used to saying polite things, loving each other, and so on. Then the teacher also uses the habituation method, the storytelling method to strengthen character, and the central learning method to maximize children's competence. Furthermore, to optimize character development, teachers also give assignments at school and at home, give consistent advice, and increase children's vocabulary by inviting them to read books. In conclusion, the formation of children's character through religious-based learning activities and methods makes young children familiar with Islamic character values, inspiring and imitating them in their daily behavior.